The Role of Audit Opinion: CEO Turnover, Financial Distress, Company Growth on Audit Opinion Shopping - Aulia Oktaviani, Ayu; Vinola Herawaty; Jul Seventa Tarigan; Irfan Rais (Universitas Yudharta Pasuruan, 2025)
Introduction; Environmental issues in coastal areas, such as the reduction of mangrove forest areas in the Pesisir Timur Surabaya (PAMURBAYA), are driven by urban development and environmentally unfriendly human activities. This phenomenon calls for entrepreneurship that adopts innovative and sustainable approaches, particularly by involving youth to create a balance between economic, social, and environmental benefits. The study aims to explore the effectiveness of Design Thinking in fostering a green entrepreneurial attitude among the youth. Method; This study focuses on the participation of business administration students in Design Thinking activities conducted at the mangrove ecotourism area in Gunung Anyar, Surabaya. A thematic analysis was performed on both research findings and current literature to gain a broader and more detailed understanding of how Design Thinking can shape sustainable entrepreneurial behavior. Results; The findings indicate that the Design Thinking process successfully encouraged students to shift their mindset viewing environmental problems as potential business opportunities. Through this process, participants were able to generate innovative and sustainability-oriented business ideas that align with green entrepreneurship principles. Conclusion; This study provides a theoretical contribution by demonstrating that Design Thinking can act as a catalyst for green entrepreneurship practices. From a practical perspective, it suggests integrating Design Thinking workshops into entrepreneurship courses to stimulate youth-led green business initiatives.